EMPIRICAL EVALUATION OF THE EXPORT COMPETITIVENESS OF INDONESIAN WOOD PRODUCTS USING RCA, RSCA, EPD, AND HYPOTHESIS TESTING (INDEPENDENT T-TEST), 2015–2024 - Latifa Salma Luva Poerawidjaja; Tria Apriliana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
The forestry sector is one of the pillars of Indonesia’s non-oil and gas exports, yet the export performance of plywood (HS 4412) fluctuated sharply during 2015–2024. This study evaluates the export competitiveness of Indonesian wood products in the global market and compares it with China and Vietnam. A descriptive quantitative approach is applied using three indicators, namely the Revealed Comparative Advantage (RCA), Revealed Symmetric Comparative Advantage (RSCA), and Export Product Dynamics (EPD), complemented by a comparison of export values through the Shapiro–Wilk normality test, Levene’s homogeneity test, and the independent sample t-test. Annual secondary data were obtained from ITC Trade Map, UN Comtrade, and BPS. The results show that Indonesia holds the highest comparative advantage, with an average RCA of 12.39 and RSCA of 0.846, although both decline gradually, while Vietnam strengthens consistently. The EPD analysis places Indonesia predominantly in the Retreat category and in the Lost Opportunity position in 2024, unlike China and Vietnam, which reach Rising Star. The t-test confirms that Indonesia’s export value differs significantly: lower than China but higher than Vietnam (sig. 0.000). Strengthening national certification, downstream processing, and market diversification are the main recommendations to maintain Indonesia’s position.